Assessment of maternal lipid profile in early pregnancy and its correlation with pregnancy outcome - Singh, Priyanka; Gupta, Renu; Lal, Pavika; Gupta, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Lipoprotein lipid physiology in pregnancy has important implications for the developing fetus as well as the mother. Elevated maternal triglycerides levels measured during early pregnancy have been associated with adverse pregnancy outcomes affecting both maternal and fetal health. Methods: This was a prospective observational study conducted in the Department of Obstetrics and Gynecology, GSVM Medical College Kanpur between January 2020 to October 2021. A total of 146 antenatal women were enrolled in this study, out of which 26 women were lost to follow-up. Lipid profile was done for each subject and was later accessed. Results: Total cholesterol were deranged in patients 30%, serum TG in 40.83%, LDL in 28.33%, HDL in 35.83%. Out of total of 120 patients, 18 (15%) patients had HDP, 6 (5%) had GDM, 13 (10.83%) had a preterm delivery, 14 (11.66%) had FGR 9 (15.83%) had SGA babies, 7 (5.83%) had LGA babies and 38 (31.66%) patients delivered by cesarean section. In this study, only 15% of the study population shows hypertensive disorder of pregnancy and had a statistically significant correlation with triglyceride level.10.83% of the study population had preterm delivery. It showed a statistically significant correlation with serum TG level. Conclusions: Estimation of serum lipid profile during pregnancy can be considered as an early and economical investigation to prevent the deleterious effects of hyperlipidaemia associated with pregnancy.